2015
DOI: 10.1007/s40685-015-0022-3
|View full text |Cite
|
Sign up to set email alerts
|

Project managers’ overconfidence: how is risk reflected in anticipated project success?

Abstract: Projects tend to exceed planned timelines and budgets. One reason may be that potential project risks are insufficiently reflected in anticipations of project success. Furthermore, project managers’ overconfidence may lead them to assess risk in a biased manner. The present study examines how risk assessment relates to overall anticipated project success and how overconfidence on the part of project managers influences such assessments. We assume that project managers’ risk awareness serves as a mediator betwe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
23
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 27 publications
(27 citation statements)
references
References 86 publications
3
23
1
Order By: Relevance
“…The results provided by Fabricius and Büttgen's (2015) contrast with the study by Rolison et al (2014), noting that older project managers' evaluate projects more optimistically due to their overconfidence. Compared to younger project managers, older project managers took more risks, which could be an explanation of higher project failure rate (Fabricius and Büttgen, 2015). Soltani et al's (2015) research in marketing demonstrated that, compared to younger managers, older managers took a more radical approach and demonstrated they were more willing to take risks.…”
Section: Riskcontrasting
confidence: 80%
See 1 more Smart Citation
“…The results provided by Fabricius and Büttgen's (2015) contrast with the study by Rolison et al (2014), noting that older project managers' evaluate projects more optimistically due to their overconfidence. Compared to younger project managers, older project managers took more risks, which could be an explanation of higher project failure rate (Fabricius and Büttgen, 2015). Soltani et al's (2015) research in marketing demonstrated that, compared to younger managers, older managers took a more radical approach and demonstrated they were more willing to take risks.…”
Section: Riskcontrasting
confidence: 80%
“…According to Henderson et al (2013), young female project managers, in contrast, were found more reluctant to take risks when than older women. Ding et al (2015) and Fabricius and Büttgen (2015) reported similar findings. Ding et al, 2015 studied the risk-taking habits of corporate board chairpersons.…”
Section: Risksupporting
confidence: 62%
“…Perception of risk goes beyond the individual and it is a social and cultural construct reflecting values, symbols, history, and ideology (Weinstein, 1989). Fabricius and Büttgen (2015) extended the knowledge in this regard by arguing that manager’s RISKP serves as a mediator between OVERCB and risk assessment linked with the decision-making process. The study focused on the mediating role of RISKP between behavioral biases and firm decisions in the United States and Pakistan.…”
Section: Resultsmentioning
confidence: 99%
“…This suggests that the more adaptive leadership is practiced in the HEIs, the better the attainment of goals could be. The result is reinforced by the findings of Ebrahimi, Moosavi, andChirani (2016), andFabricius andBüttgen (2015), who described that to secure organizational success, leaders must utilize adaptive leadership strategies. In addition, the results of this study were consistent with Nolan (2017), who stated that effectiveness in organizations depended on the effectiveness of their leaders, and adaptive leadership was the cornerstone of organizational effectiveness.…”
Section: Relationship Between Adaptive Leadership and Organizational Effectivenessmentioning
confidence: 99%